2.4k views
9 votes
-2x - y = 1
-6x=3y+3

User AGE
by
5.4k points

1 Answer

6 votes

Answer: All Real Number

Explanation:

This is a system of equation, and generally, there are three ways to solve:

  • elimination
  • substitution
  • augmented matrix

Here, we are going to use elimination

------------------------------------------------------------------------------------

Given

-2x-y=1

-6x=3y+3

Put them in the same order

-2x-y=1

-6x-3y=3

Multiply 3 on both sides for the first equation

-6x-3y=3

-6x-3y=3

We subtract the first equation from the second equation

0=0

The answer will be All Real Numbers, which means any real number will fit this equation. In the graphing method, these two equations will overlap each other.

Hope this helps!! :)

Please let me know if you have any questions

User Pavel Molchanov
by
4.8k points